Reinerantha foliicola, a new genus and species of Lejeuneaceae subtribe Cololejeuneinae (Marchantiophyta) from Ecuador. Issue 1 (14th December 2017) - Gradstein, S. Robbert; Zhu, Rui‐Liang; Shu, Lei; Pérez, Álvaro J.
Abstract: Cololejeuneinae is the largest subtribe of the liverwort family Lejeuneaceae and the crown group of the family. The species often grow on the surfaces of living leaves and twigs or in swiftly running waters and many of them possess neotenic gametophytes, considered an adaptation to these extreme habitats. We describe a new, epiphyllous genus and species in Cololejeuneinae from the Western Cordillera of Ecuador, Reinerantha foliicola Gradst. & R.L.Zhu. Analysis of combined molecular datasets with parsimony, maximum likelihood and Bayesian methods revealed Reinerantha in a sister relationship to the large pantropical genus Diplasiolejeunea . Reinerantha differs from Diplasiolejeunea in leaf segmentation, epidermal wall thickening, stylus, male bracts and perianth keels, and is morphologically more similar to the genus Tuyamaella . In the molecular analysis, however, Reinerantha and Tuyamaella were resolved in different clades and not closely related. Tuyamaella is shown to be restricted to Asia; the report of Tuyamaella from South America (Peru) was erroneous and a case of mislabeling.